ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PERIODE 2011-2014 - Aditya Setiawan, I Putu Doni; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2018)
Achieving synergies is the goal of companies performing mergers and acquisitions while improving the company's financial performance. This study aims to determine whether there is an increase in financial performance in companies experienc ed financial distress and who did not experience financial distress for five years before and two years after mergers and acquisitions. The companies were selected using purposive sampling method to obtain 33 samples. The company's financial performance is measured by five ratios: Current Ratio (CR), Return on Asset (ROA), Return on Equity (ROE), Debt to Equity (DER) and Total Asset Turnover (TATO). Analytical techniques used in this study are altman z-score, descriptive statistical test, normality test and paired sample t test. The test results show that the financial performance of companies experiencing financial distress and companies that do not experience financial distress did not experience an increase after mergers and acquisitions Keywords: financial performance, financial distress, mergers and acquisitions